Clinical cases of tattoo-associated dermatoses - Makurina, H. I.; Cherneda, L. O.; Dolia, O. S. (Modern medical technology, 2023)
The aim of the work is to analyze clinical cases of tattoo-associated skin reactions as an example of the algorithm of differential diagnosis of dermatoses of this group. Materials and methods. The personal observation of two clinical cases related to tattooing for aesthetic reasons and the appearance of a pathological reaction on the skin after the introduction of dyes is described. In addition to the visual assessment of the clinical picture, the final confirmation of the diagnosis was based on pathohistological examination. Results. Variability of clinical manifestations associated with tattooing is presented. The first clinical case is represented by the symmetrical appearance of a rash in the form of small papules up to 0.3–0.4 cm in diameter with clear borders, pink in color, and rounded in shape in the area of the eyebrows after their tattooing. Morphologically, the effect of black pigment on the skin in this case is represented by non-specific granulomatous inflammation. The second clinical case is characterized by the appearance of a plaque with hyperkeratosis phenomena and subjective complaints of slight itching at the site of red tattoo dye injection. Pathohistological examination indicated dermatitis of the mixed group (lichenoid interface and granulomatous), which is most correspond to an allergic reaction to tattoo pigment. Conclusions. The increase in the number of patients with tattoos requires a wider consideration of the complications that can be provoked by the artificial injection of dyes into the skin. Despite the advantage of allergic complications after tattooing, the risk of systemic diseases should raise the level of vigilance of practicing physicians regarding the timely diagnosis of sarcoidosis or aggressive neoplasia. The pathohistological examination is the “gold standard” for the final verification of complications after the artificial injection of pigment into the skin.